História natural de Crossodactylus schmidti Gallardo, 1961 (Anura, Hylodidae) no Parque Estadual do Turvo, Rio Grande do Sul - Caldart, Vinícius Matheus (2011)
This dissertation presents information on (1) the advertisement and aggressive calls of Crossodactylus schmidti and on (2) the species diet and its relationship with prey availability. The study was conducted with populations from the Parque Estadual do Turvo, located in the northwestern region of Rio Grande do Sul, Brazil. The park has an area of 17,491.4 ha and constitutes the largest preserved remnant of Mesophytic Semideciduous Forest in the state of Rio Grande do Sul. The advertisement and aggressive calls of C. schmidti were described based on vocalizations of seven individuals recorded between October 2009 and February 2010. Compared to the advertisement calls described for other species of the genus, the advertisement call of C. schmidti differs in the temporal structure by having fewer notes per call and longer intervals between notes, and in the spectral structure by having lower values of dominant frequency. The aggressive call of C. schmidti is a variation of the advertisement call, which is similar to this in the note duration and dominant frequency values, but is a longer call, having fewer notes with longer intervals between them. The advertisement and aggressive calls of C. schmidti may be emitted separately, or the aggressive call may be followed by the advertisement call. The diet of C. schmidti was evaluated from September 2009 to March 2010, based on 93 stomach contents obtained by the technique of regurgitation (n= 80) and analysis of stomach contents of collected specimens (n= 13). In this study we determined the diet niche breadth, evaluated the relationship of diet composition with prey availability in the environment, and we also looked for ontogenetic and sexual changes and composition differences in the diet. Nineteen categories of prey were consumed, and ants, beetles and flies presented the highest importance values. Despite the varied diet, the diet niche breadth was low, with few prey categories predominantly consumed. Ants, flies and spiders were consumed in similar proportion to that estimated in the environment. There was no relationship between mouth width and length and/or volume of prey consumed, but the differences in diet composition between males and females, and between adults and juveniles, were significant. Considering the varied diet, the relationship between the most important items of diet with their availability in the environment, and the narrow niche breadth found, C. schmidti seems to be an opportunistic forager with feeding habits similar to other species of the genus. The similarities in the importance of items such as ants, beetles, flies and insect larvae in diet of C. schmidti and other species of the genus suggest a strong phylogenetic influence.